Analisis Tingkat Over Tourism di Kawasan Wisata Sejarah Cirebon - Ni Gusti Made Kerti Utami; Erfin Roesfian; Maksum Suparman; Asdiansyah Saputra (Journal of Mandalika Review, 2023)
Today, tourism development is rapidly growing, and it is easy for potential tourists to access information about a tourist destination. These conditions have an impact on increasing tourist visits. In addition, this phenomenon can also increase damage to existing tourist attractions because the number of visits exceeds the available capacity or exceeds the capacity of the tourist attraction itself. In this regard, easy access to the Cirebon Historical Tourism Area also causes discomfort for the local community. So it is necessary to measure it to determine the level of over tourism in the Cirebon Historical Tourism Area. By analyzing how the condition of over tourism is in the Cirebon Historical Tourism Area, it can also be seen that the factors can be applied to various tourist destinations in Indonesia to measure the level of over tourism. The design of this study uses quantitative research methods with descriptive statistical data analysis techniques. The population in this study are tourism stakeholders in the Cirebon Historical Tourism Area. This sampling technique used incidental sampling and purposive sampling. In this case, the samples taken are tourism stakeholders who live in the Cirebon Historical Tourism Area. In general, the historical tourism area of Cirebon has over tourism in a high position (3.61 on a scale of 1 – 5), with various indicators still pointing to possibilities for improvement. The stakeholders who must improve this condition are the management of seven of the nine indicators, and the local government must complete two of the nine indicators. It needs fast treatment to improve the quality of tourist attractions in the historical tourist area of Cirebon to improve the people's economy. It is hoped that in the future, further research can be carried out on the conditions in detail that cause over tourism in description and cause and effect.